Relationship between food insecurity and diabetes among patients in Saudi Arabia - Hanbazaza, Mahitab; Alzahrani, Sami; Makki, Ghada; Almihmadi, Ghalia; Mohammed, Nawahil (Progress in Nutrition, 2022)
Background: Food insecurity (FI) is a major determinant of nutritional status, which could influence the self-care practices of diabetic patients. Objective: To assess the prevalence of FI and examine the relationship between FI and self-management practices among patients with diabetes. Methods: A cross-sectional survey was conducted on 229 patients at the diabetes clinic in King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Results: The prevalence of FI was 26.2%, and it was more prevalent among non-Saudis, unemployed participants, and those with low household incomes (<5,000 SAR), as compared to food secure group (p <0.0001 for all comparisons). FI significantly predicted higher odds of irregular self-monitoring of blood glucose (OR = 2.47, 95% CI, 1.14–5.37, p = 0.022). Additionally, FI significantly predicted cost-related non-adherence to medication use (β = 1.95, 95% CI, 1.60–2.29, p <0.0001), and hypoglycemia-related complications (β = 0.69, 95% CI, 0.50–0.88, p <0.0001). These indicators were significantly influenced by severe FI. The intake of unhealthy food moderated the relationship of FI with hypoglycemia and its related complications (β = 0.11, 95% CI, 0.03–0.18, p = 0.006). Conclusions: Food assistance coverage and health awareness programs are required to support food insecure diabetic patients, a step that could optimize their healthy food choices and self-management practices.